Tactile Sensors: Rapid Manufacturing of Mechanoreceptive Skins for Slip Detection in Robotic Grasping (Adv. Mater. Technol. 1/2017). Issue 1 (January 2017) - Charalambides, Alexi; Bergbreiter, Sarah
Abstract : In article number 1600188, Alexi Charalambides and Sarah Bergbreiter present a rapid manufacturing process using computerized numerical control (CNC) milling to create a "robot skin" with normal and shear force tactile sensing. The robot skin is made entirely of elastomer and contains tactile pixels with microscale features distributed over a large area. Using this approach, the robot skin is integrated with a 1 degree‐off‐reedom gripper for closed‐loop grasping and slip detection.